Project Bug: um VR-serious game para o processo de controle biológico de insetos - Jesus, Arthur Willian Ferraz de (2024)
This paper presents the development and preliminary evaluation of the game Project Bug VR, a serious Virtual Reality game for teaching entomology, which uses interaction techniques for 3D interfaces to simulate the process of biological control of insects between aphids and parasitoids. We developed this game inspired by the Survivor Horror style using resources from the Unity game engine, the XR Interaction Toolkit package, and Meta Quest 2. We executed a pilot study applying questionnaires to evaluate the system’s usability (System Usability Scale), the user experience (User Experience Questionnaire), and the pre and post-game expectations, as well as to collect qualitative aspects of the game. Eight volunteer participants took part in the experiment. The evaluations were positive, highlighting the ease of use of the solution (x=6.12), as well as aspects of originality (x=6.12), interesting application (x=6.50), efficient (x=5.62) and exciting (x=5.87) in the user experience. The average usability score reached 78.75, which indicates good acceptability of the solution and available resources. Fromthe results, we can highlight that Project Bug VR has the potential to be an effective support tool for teaching entomology.